Tissue and salinity specific Na+/Cl− cotransporter (NCC) orthologues involved in the adaptive osmoregulation of sea lamprey (Petromyzon marinus) - A. Barany (Nature Portfolio, 2021)
Abstract Two orthologues of the gene encoding the Na+-Cl− cotransporter (NCC), termed ncca and nccb, were found in the sea lamprey genome. No gene encoding the Na+-K+-2Cl− cotransporter 2 (nkcc2) was identified. In a phylogenetic comparison among other vertebrate NCC and NKCC sequences, the sea lamprey NCCs occupied basal positions within the NCC clades. In freshwater, ncca mRNA was found only in the gill and nccb only in the intestine, whereas both were found in the kidney. Intestinal nccb mRNA levels increased during late metamorphosis coincident with salinity tolerance. Acclimation to seawater increased nccb mRNA levels in the intestine and kidney. Electrophysiological analysis of intestinal tissue ex vivo showed this tissue was anion absorptive. After seawater acclimation, the proximal intestine became less anion absorptive, whereas the distal intestine remained unchanged. Luminal application of indapamide (an NCC inhibitor) resulted in 73% and 30% inhibition of short-circuit current (Isc) in the proximal and distal intestine, respectively. Luminal application of bumetanide (an NKCC inhibitor) did not affect intestinal Isc. Indapamide also inhibited intestinal water absorption. Our results indicate that NCCb is likely the key ion cotransport protein for ion uptake by the lamprey intestine that facilitates water absorption in seawater. As such, the preparatory increases in intestinal nccb mRNA levels during metamorphosis of sea lamprey are likely critical to development of whole animal salinity tolerance.